SPECIAL EDUCATION TEACHERS’ KNOWLEDGE AND SKILLS IN TEACHIKNG ENGLISH TO DEAF STUDENTS IN SIDOARJO (RETAIN, 2017)
SPECIAL EDUCATION TEACHERS’ KNOWLEDGE AND SKILLS IN TEACHIKNG ENGLISH TO DEAF STUDENTS IN SIDOARJO Nanky Pradhina Yuana English Department, Faculty of Languages and Arst, State University of Suabaya, nanyyuana@mhs.unesa.ac.id Ahmad Munir, Ph.D English Department, Faculty of Languages and Arst, State University of Suabaya, ahmadmunir@unesa.ac.id Abstrak Penelitian ini berkaitan pengetahuan dan ketrampilan guru sekolah luar biasa dalam mengajar Bahasa Inggris untuk anak tuna rungu. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana kemampuan guru sekolah luar biasa yang tidak memiliki pengetahuan dalam mengajar Bahasa Inggris mengajarkan Bahasa Inggris pada siswa tuna rungu didalam kelas. Penelitian kualitatif digunakan dalam penelitian ini. Enpat guru sekolah luar biasa dari beberapa kawasan di Sidoarjo terpilih sebagai subyek dari penelitian ini. Data dikumpulkan melalui wawancara nara sumber dan observasi proses pembelajaran. Kemudian, data dianalisis secara kualitatif. Penelitian ini menemukan dua hasil. Pertama, guru sekolah luar biasa di Sidoarjo memiliki pengetahuan kurang dari yang dibutuhkan untuk mengajarkan Bahasa Iggris untuk siswa tuna rungu. Kedua, kurangnya pengetahuan yang mereka miliki membatasi ketrampilan mereka dalam mengajarakan Bahasa Inggris untuk siswa tuna rungu yang juga menyebabkan mereka tidak dapat disebut sebagai guru professional. Kata Kunci: guru professional, guru sekolah luar biasa, tuna rungu, pengetahuan, ketrampilan Abstract This study deals with special education teachers’ knowledge and skills in teaching English to deaf students. The objectives of this study are to find out how does special education teacher who teach English without background knowledge in teaching English do an English teaching in the classroom. A qualitative research was applied in this research. Four special education teachers from all around Sidoarjo was chosen as the subject of this study. The data were collected by interviewing the subject of the study and observation of the learning process. Then, the data were analyzed qualitatively. This study found two results. First, the special education teachers in Sidoarjo have little knowledge than it is needed to be able to teach English to deaf students. Second, their lack of knowledge limit their skills in teaching English to deaf students which also cause them cannot be called as professional teacher. Keywords: professional teacher, special education teacher, deaf, knowledge, skills